The female character: a postcolonial feminist perspective of the selected novels by J.M. Coetzee - Suadah Jasim Salih (Tanjong Malim, 2022)
The female character: a postcolonial feminist perspective of the selected novels by J.M. Coetzee by Suadah Jasim Salih